Autism presentation in female and Black populations: Examining the roles of identity, theory, and systemic inequalities. (November 2022) - Diemer, Maire Claire; Gerstein, Emily D; Regester, April
The prevalence of autism is rising, a dynamic attributed to numerous explanations (e.g. better diagnostic practices, decreased stigma). As this neurodevelopmental disability increases in visibility, disparities in its diagnostic rate grow. Female and Black populations in the United States have historically lower prevalence, are diagnosed later, are more likely to have co-occurring intellectual disability, and experience exclusion from research. Autistic Black girls are effectively invisible in the literature. To combat this exclusion, this narrative review discusses intersectionality theory and how it may be used to provide integrated models that are inclusive toward diverse gender, ability, and racial/ethnic backgrounds. Systemic inequalities, including prenatal care and misdiagnosis, disproportionately negatively impact the quality of care available to female and Black autistic populations. The authors recommend that research include autistic populations with co-occurring intellectual disability, include a diagnostic evaluation as part of protocols, and clinically, universal screening and improved provider competence and confidence in working with diverse autistic populations. Lay abstract: Although the prevalence of autism has been rising in recent years, disparities in diagnosis still remain. Female and Black populations in the United States are diagnosed later, are more likely to have an intellectual disability, and are excluded from research as well as services designed for autistic individuals. Autistic Black girls are effectively invisible in the current scientific literature. Intersectional theory, which looks at a person as a whole, examines models that are inclusive toward diverse gender, ability, and racial/ethnic backgrounds. This theory may be a useful approach to clinical and research work with autism so that practitioners may be most effective for the whole population of autistic people. The authors recommend research focusing on inclusion of autistic populations with intellectual disability and research studies that include evaluations as part of the procedure. Clinically, the authors recommend a focus on screening all young children for autism and improving provider knowledge in working with diverse autistic populations.